Association between social networks and cognitive impairment among older Chinese adults: the mediating effect of depression - Zhang, Zhuo; Bian, Ying (Frontiers in Aging Neuroscience, 2025)
ObjectivesThis study aimed to explore the rationality of the social networks-depression-cognitive impairment pathway and to provide recommendations for the development of mild cognitive impairment intervention strategies.MethodsA cross-sectional survey was conducted in 2021. Sixteen urban communities in Xi 'an, Shaanxi China were selected as sample sites. The cognitive function, social networks and depression were measured by the Montreal Cognitive Assessment (MoCA), the Lubben Social Network Scale-6 (LSNS-6) and the Geriatric Depression Scale-15 (GDS-15), respectively. The generalized linear model was used to analysis the impact of social networks on cognitive impairment, and further analysis the mediating effect of depression.ResultsA total of 745 elderly people aged 60 and above was included in this survey, with an average age of 68.90 ± 6.00 years. The prevalence of cognitive impairment was 18.52%, and the prevalence of cognitive impairment increased with age. According to the generalized linear model, poor social networks (relative network, friend network) was associated with higher risk of cognitive impairment (OR = 2.08, 95% CI: 1.27–3.41), and this association was more significant in women and older adults <70 years of age. Mediation analysis results showed that depression was the mediating path between social networks and cognitive impairment, with the indirect effects accounting for 34.44%.ConclusionSocial isolation increases the risk of cognitive impairment and depression has a significant mediating effect on the relationship between social isolation and cognitive impairment.